1999
DOI: 10.1056/nejm199903043400916
|View full text |Cite
|
Sign up to set email alerts
|

Zygotic Splitting after Assisted Reproduction

Abstract: We cannot acknowledge receipt of your letter, but we will notify you when we have made a decision about publication. We are unable to provide prepublication proofs. Please enclose a stamped, self-addressed envelope if you want unpublished material returned to you. Financial associations or other possible conflicts of interest must be disclosed. Submission of a letter constitutes permission for the Massachusetts Medical Society, its licensees, and its assignees to use it in the Journal' s various editions (prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 5 publications
1
43
0
Order By: Relevance
“…This view, however, is not warranted on the basis of critical appraisal of available data and, moreover, fails to take account of various findings that remain unexplained (Gardner 2001b). Among these is why the frequency of monozygotic twinning is significantly higher following assisted than natural conception in our own species (Derom et al 1987;Wenstrom et al 1993;Blickstein et al 1999). As this mode of twinning is associated with an increased risk of congenital malformation (Schinzel et al 1979;Szymonowicz et al 1986;Little & Bryan 1988;Hall 1996), the continuing expansion of assisted reproductive practices lends particular urgency to the task of ascertaining the nature and significance of prepatterning in mammals.…”
Section: Discussionmentioning
confidence: 96%
“…This view, however, is not warranted on the basis of critical appraisal of available data and, moreover, fails to take account of various findings that remain unexplained (Gardner 2001b). Among these is why the frequency of monozygotic twinning is significantly higher following assisted than natural conception in our own species (Derom et al 1987;Wenstrom et al 1993;Blickstein et al 1999). As this mode of twinning is associated with an increased risk of congenital malformation (Schinzel et al 1979;Szymonowicz et al 1986;Little & Bryan 1988;Hall 1996), the continuing expansion of assisted reproductive practices lends particular urgency to the task of ascertaining the nature and significance of prepatterning in mammals.…”
Section: Discussionmentioning
confidence: 96%
“…A second interpretation is that these monochorionic placentas result from the fusing of dizygous twins, which is an extremely rare phenomenon that has been recently reported in ART-derived twins (Miura & Niikawa, 2005;Souter et al, 2003). Regarding the first interpretation, some investigators have reported that ART promotes monozygous twinning (Alikani et al, 2003;Behr et al, 2000;Blickstein et al, 1999;Derom et al, 2001;Milki et al, 2003;Schachter et al, 2001), reporting values roughly two to 12 times the expected 0.4% monozygous twinning rate of all births from the general population (Bulmer, 1970). To explain the role of ART in monozygous twinning, various mechanistic hypotheses have been put forth, such as oral contraceptive use (Bressers et al, 1987;Macourt et al, 1982;Rothman, 1977), gonadotrophin therapy for ovarian hyperstimulation (Schachter et al, 2001), calcium reduction (Steinman, 2002;Steinman & Valderrama, 2001), zona pellucida micromanipulation (Alikani et al, 1994;Saito et al, 2000;Schieve et al, 2000;Slotnick & Ortega, 1996), blastocyst embryo transfer (Behr et al, 2000;da Costa et al, 2001;Milki et al, 2003), and the transfer of a high number of embryos (Sills et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In the FASTER trial, patients aged 35-39 years were at increased risk to a deliver low birthweight neonate (adjusted OR 1.6) (Cleary-Goldman, . In addition, Salem-Yaniv et al, in a retrospective population based study found a significant increase in low birth weight among older women (35)(36)(37)(38)(39)(40) 144,018). This study has found that the odds of low birth weight were reduced with increasing maternal age and with a history of a previous pregnancy (either spontaneous or following IVF) (Nelson and Lawlor, 2011).…”
Section: The Effect Of Maternal Age On Reproduction and Pregnancy Outmentioning
confidence: 99%
“…In 2008, among the ART cycles that used fresh non-donor eggs or frozen-thawed embryos and progressed to the embryo transfer stage, approximately 38% involved the transfer of three or more embryos, about 13% of cycles involved the transfer of four or more embryos, and approximately 4% of cycles involved the transfer of five or more embryos. In addition, ART conceived pregnancies have a higher rate of zygotic splitting in cycles were a single embryo was transferred resulting in increased rate of monochorionic twins than spontaneously conceived pregnancies (Blickstein, Jones et al, 2003;Blickstein, Verhoeven et al, 1999). Among the 38,631 pregnancies that resulted from ART cycles using fresh nondonor eggs or embryos, approximately 61% were singleton, 29% were twins, and about 4% were triplets or more.…”
Section: The Association Between Art and Multiple Gestationsmentioning
confidence: 99%